Świat natury w twórczości Ryszarda Kapuścińskiego - Kusiak , Wojciech (Colloquia Litteraria, 2024)
Ryszard Kapuscinski admired the beauty and richness of nature. As a reporter, foreign and war correspondent, writer, poet and a photographer, sometimes he experienced difficulties in describing the reality that surrounded him. Even more so when it concerned phenomena occurring in geographically distant and culturally foreign areas. While delighting in the ecosphere, Kapuscinski adopted an anthropocentric attitude. He considered people to be his most natural environment. Referring to the conceptual apparatus of the philosophy of dialogue, it can be argued that for him nature was a stage of an encounter with another human being.